Slavs in the United States - Hayden, Joel B.; Miller, Kenneth D.; Lusk, Davis W.; Cihelski, L.; Smetanka, Jaroslav F.; Duncan, William Y. ([Board of National Missions of the Presbyterian Church in the U.S.A.])
Five pamphlets in folder: The Poles in the United States / by Joel B. Hayden -- The Yugoslavs in the United States / by Kenneth D. Miller -- The Ukrainians in the United States / by Davis W. Lusk, D.D. and L. Cihelski -- The Czechoslovaks in the United States / by Jaroslav F. Smetanka -- The Russians in the United States / by William Y. Duncan.